1996
DOI: 10.1046/j.1365-2249.1996.d01-755.x
|View full text |Cite
|
Sign up to set email alerts
|

Histaminergic regulation of interferon-gamma (IFN-γ) production by human natural killer (NK) cells

Abstract: SUMMARYMonocytes, recovered from human peripheral blood by counter-current centrifugal elutriation, effectively inhibit the production of IFN-°by CD3 ÿ /56 NK cells in response to IL-2. This study aimed at defining the nature of the inhibitory signal, particularly the importance of monocyte-derived reactive metabolites of oxygen. It was found that monocytes recovered from patients with chronic granulomatous disease (CGD), a condition characterized by deficient NADPH-oxidase activity of phagocytes, did not inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
(35 reference statements)
1
9
0
Order By: Relevance
“…This finding corroborates previous studies showing that superoxide radicals down-regulate most NK cell functions (22,23,(35)(36)(37)(38)(39). NK cells rapidly migrate to extravascular sites to attack and destroy altered target cells (40), and they are therefore especially important in controlling HSV infections in which the virus-infected cells otherwise escape CD8 ϩ T cell-mediated destruction as a consequence of the virus-induced downmodulation of MHC class I expression.…”
Section: Discussionsupporting
confidence: 91%
“…This finding corroborates previous studies showing that superoxide radicals down-regulate most NK cell functions (22,23,(35)(36)(37)(38)(39). NK cells rapidly migrate to extravascular sites to attack and destroy altered target cells (40), and they are therefore especially important in controlling HSV infections in which the virus-infected cells otherwise escape CD8 ϩ T cell-mediated destruction as a consequence of the virus-induced downmodulation of MHC class I expression.…”
Section: Discussionsupporting
confidence: 91%
“…Functionally, CGD cells have been shown to display prolonged intracellular calcium transients upon stimulation, leading to exaggerated cellular responses [26]. ROS have also been implicated in numerous processes of potential importance for the inflammatory conditions displayed by CGD patients: neutrophil cell death (both apoptosis [27] and necrosis [28]), secondary clearance of apoptotic cells [29,30], and functional downregulation of immunocompetent lymphocytes [31]. In addition, rats with decreased capacity to produce ROS display increased susceptibility to autoimmune arthritis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Because IL-18 up-regulates perforin-mediated NK activity (46) and histamine was reported to enhance NK cell activity (47), it is possible that the effect of histamine on NK activity may be mediated by IL-18 secretion. Dohlsten et al (48) observed that histamine inhibited the production of IFN-␥ in activated PBMCs, while Asea et al reported that histamine enhanced the production of IFN-␥ in NK cells cocultured with monocytes by reducing monocytic production of reactive oxygen species (49). Both effects were reported to be mediated by H 2 receptors (48, 49), suggesting that H 2 receptors are present on many subsets of lymphocytes and that the stimulation of these receptors differentially regulates the production of IFN-␥ depending on the activation state of each subset.…”
Section: Discussionmentioning
confidence: 99%